The concept and measurement of violence against women and men Sylvia Walby [and eleven others]. - Walby, Sylvia (Policy Press shorts. Policy & practice., 2017)
Both a guide to international debate on the measurement of gender-based violence (GBV) for policy purposes and a handbook on how those measurements can be best achieved, this book draws on cutting-edge statistical research to propose new measurement methods designed for promoting gender equality in the contemporary world.